Determination of dominant recombination site in perovskite solar cells through illumination-side-dependent impedance spectroscopy - Omer, Mohamed I. (2022)
Perovskite solar cells (PSCs) have attracted wide attention due to their capacity to achieve high-power conversion efficiencies. However, the high trap-assisted recombination taking place in the active layer leads to performance loss in PSCs. In particular, the excessive recombination at the interface between the perovskite active layer and the carrier selective contacts can be especially problematic. Therefore, the identification of the dominant recombination pathways in a given PSC architecture is of significant importance for the mitigation of losses and enhancement of device performance. Here, we introduce an approach for identifying the dominant recombination pathways in PSCs by applying illumination-side-dependent impedance spectroscopy (ISD-IS) measurements on the devices with a semi-transparent top electrode. We validate this technique using coupled ionic-electronic numerical simulations and apply it experimentally on a standard PSC structure. Overall, this approach could be of significant importance for pinpointing the performance bottlenecks in PSC devices under operationally relevant conditions and providing a more detailed picture of the losses in a complete PSC device by examining its behaviors under illumination from both sides at different operation conditions, which could allow for a more targeted optimization strategy of PSCs to improve their performance.